Genetic associations with technical capabilities in English academy football players: a preliminary study - Mcauley, A. B.; Hughes, D. C.; Tsaprouni, L. G.; Varley, I.; Suraci, B.; Baker, J.; Herbert, A. J.; Kelly, A. L. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Technical capabilities have significant discriminative and prognostic power in youth football. Although, many factors influence technical performance, no research has explored the genetic contribution. As such, the purpose of this study was to examine the association of several single nucleotide polymorphisms (SNPs) with technical assessments in youth football players. METHODS: Fifty-three male under-13 to under-18 outfield football players from two Category 3 English academies were genotyped for eight SNPs. Objective and subjective technical performance scores in dribbling, passing, and shooting were collated. Simple linear regression was used to analyse individual SNP associations each variable, whereas both unweighted and weighted total genotype scores (TGSs; TWGSs) were computed to measure the combined influence of all SNPs. RESULTS: In isolation, the ADBR2 (rs1042714) C allele, BDNF (rs6265) C/C genotype, DBH (rs1611115) C/C genotype, and DRD1 (rs4532) C allele were associated with superior (8-10%) objective dribbling and/or shooting performance. The TGSs and/or TWGSs were significantly correlated with each technical assessment (except subjective passing), explaining up to 36% and 40% of the variance in the objective and subjective assessments, respectively. CONCLUSIONS: The results of this study suggest inter-individual genetic variation may influence the technical capabilities of youth football players and proposes several candidate SNPs that warrant further investigation.